Intelligent robot motion control system Part I: System overview and image recognition - Yuan-Wei Tseng; Chang-Meng Li; Lee, Alan; Guo-Cin Wang (2013 International Symposium on Next-Generation Electronics, 2013)
The purpose of this paper is to design an intelligent wheel robot, which can recognize and follow a predefined forward sign while automatically bypassing any encountered obstacle. By distributing those forward signs, the path of the robot is determined. With this concept, an image based autopilot system with immunity against electromagnetic interference is constructed. Harr-like feature training algorithm in OpenCV has been applied so that the robot can quick detect the forward sign. The rotation of the robot for automatic target detecting is achieved by fuzzy control. The experimental results showed that the robot could successfully detect forward sign and response properly. Consequently, the proposed design approach is proven to be workable. Simply redistributing the recognizable signs by the robot, a new path for robot is constructed. Therefore, it has great flexibility for applications. The detail will be presented in part II.